Presence of diabetes mellitus and steatosis is associated with liver stiffness in a general population: The Rotterdam study. Issue 1 (1st October 2015) - Koehler, Edith M.; Plompen, Elisabeth P.C.; Schouten, Jeoffrey N.L.; Hansen, Bettina E.; Darwish Murad, Sarwa; Taimr, Pavel; Leebeek, Frank W.G.; Hofman, Albert; Stricker, Bruno H.; Castera, Laurent; Janssen, Harry L.A.
Abstract : Given that little is known about the prevalence of, and factors associated with, liver fibrosis in the general population, we aimed to investigate this in a large, well‐characterized cohort by means of transient elastography (TE). This study was part of the Rotterdam Study, a population‐based study among individuals ≥45 years. All participants underwent abdominal ultrasound and TE. Liver stiffness measurement (LSM) ≥8.0 kilopascals (kPa) was used as a cutoff suggesting clinically relevant fibrosis. Of 3, 041 participants (age, 66.0 ± 7.6 years) with reliable LSM, 169 (5.6%) participants had LSM ≥8.0 kPa. Age (odds ratio [OR]: 2.40; 95% confidence interval [CI]: 1.72‐3.36; P < 0.001), alanine aminotransferase (ALT; OR, 1.24; 95% CI: 1.12‐1.38; P < 0.001), smoking (OR, 1.77; 95% CI: 1.16‐2.70; P = 0.008), spleen size (OR, 1.23; 95% CI: 1.09‐1.40; P = 0.001), hepatitis B surface antigen, or anti–hepatitis C virus positivity (OR, 5.38; 95% CI: 1.60‐18.0; P = 0.006), and combined presence of diabetes mellitus (DM) and steatosis (OR, 5.20; 95% CI: 3.01‐8.98; P < 0.001 for combined presence) were associated with LSM ≥8.0 kPa in multivariable analyses. The adjusted predicted probability of LSM ≥8.0 kPa increased per age decade, with probabilities ranging from 1.4% (0.9‐3.6) in participants ages 50‐60 years to 9.9% (6.8‐14.5) in participants >80 years. Participants with both DM and steatosis had the highest probabilities of LSM ≥8.0 kPa (overall probability: 17.2% [12.5‐23.4]; this probability did not increase with age [ P = 0.8]). Conclusion : In this large population‐based study of older adults, LSM ≥8.0 kPa, suggestive of clinically relevant fibrosis, was present in 5.6% and was strongly associated with steatosis and DM. In the context of an aging population and an increased prevalence of DM and obesity, this study illustrates that liver fibrosis may become a more prominent public health issue in the near future. (Hepatology 2016;63:138–147)